CREDIT SUPPORT FOR PRIMARY AGRICULTURAL MANUFACTURERS IN SERBIA (PERIOD 2004-2006) - Paraušić, Vesna; Cvijanović, Drago (Economics of Agriculture, 2006)
Financial problem of domestic agricultural is momentary, but in many years ago, current matter in economy in Serbia. Almost every problem and hindrance of agricultural development arise from deficiency finance resorurces and nonexisting plain model of agricultural finansing. Assistance of the Ministry of agricultural and Fund for Vojvodina development is insufficient (in 2005. only 18% registered economy, apropos 3,2% rostered economy attained credit support from national budget), but this support is very important, especially, because in the domestic market commercial banks offer unfavourable credits for primary agricultural manufacturers. What is positive in this field is that budgetary source for agriculural from years to years get rise, and we have to belave that in future, with rise of bank number and progress of competitve, financial soruse will be more accessible for domestic agricultural producers.